Genetic heterogeneity of motor neuropathies. (28th March 2017) - Bansagi, Boglarka; Griffin, Helen; Whittaker, Roger G.; Antoniadi, Thalia; Evangelista, Teresinha; Miller, James; Greenslade, Mark; Forester, Natalie; Duff, Jennifer; Bradshaw, Anna; Kleinle, Stephanie; Boczonadi, Veronika; et al.
Abstract : Objective: To study the prevalence, molecular cause, and clinical presentation of hereditary motor neuropathies in a large cohort of patients from the North of England. Methods: Detailed neurologic and electrophysiologic assessments and next-generation panel testing or whole exome sequencing were performed in 105 patients with clinical symptoms of distal hereditary motor neuropathy (dHMN, 64 patients), axonal motor neuropathy (motor Charcot-Marie-Tooth disease [CMT2], 16 patients), or complex neurologic disease predominantly affecting the motor nerves (hereditary motor neuropathy plus, 25 patients). Results: The prevalence of dHMN is 2.14 affected individuals per 100, 000 inhabitants (95% confidence interval 1.62–2.66) in the North of England. Causative mutations were identified in 26 out of 73 index patients (35.6%). The diagnostic rate in the dHMN subgroup was 32.5%, which is higher than previously reported (20%). We detected a significant defect of neuromuscular transmission in 7 cases and identified potentially causative mutations in 4 patients with multifocal demyelinating motor neuropathy. Conclusions: Many of the genes were shared between dHMN and motor CMT2, indicating identical disease mechanisms; therefore, we suggest changing the classification and including dHMN also as a subcategory of Charcot-Marie-Tooth disease. Abnormal neuromuscular transmission in some genetic forms provides a treatable target to develop therapies.